Aboriginal Worlds and Australian Capitalism. (1st November 2021) - Norman, Heidi
Abstract : Australia has a fairly established literature that seeks to explain, on one hand, the pre-colonial Aboriginal society and economy and, on the other, the relationship that emerged between the First Peoples' economic system and society, and the settler economy. Most of this relies on theoretical frameworks that narrate traditional worlds dissolving. At best, these narratives see First Peoples subsumed into the workforce, retaining minimal cultural residue. In this paper, I argue against these narratives, showing the ways Aboriginal people have disrupted, or implicitly questioned and challenged dominant forms of Australian capitalism. I have sought to write not within the earlier framework of what is called Aboriginal History that often concentrated on the governance of Aborigines rather than responses to governance. In doing this, I seek to bring into view a history of Aboriginal strategies within a capitalist world that sought to maintain the most treasured elements of social life – generosity, equality, relatedness, minimal possessions, and a rich and pervasive ceremonial life.